Crocs and Gators - Beaver, Simon (New York Cambridge University, 2014)
Come explore the fascinating lives of crocodilians. These ancient and dangerous animals make great shoes, food, and more!
Cambridge Discovery Education Interactive Readers are the next generation of graded readers - captivating topics, high-impact video, and interactive exercises designed to motivate and engage.
Glossary, Contents.
Keywords: English language; Animals; Elementary level